REKONSTRUKSI METODOLOGI STUDI ISLAM (MSI) (Merubah Nalar Dan Bertindak Kosmopolitan) - Iswahyudi, Iswahyudi (IAIN Ponorogo, 2015)
Abstract: Two aspects in Islamic teachings are normative and historical aspects. These two aspects are always intertwined throughout history. However, there are some Muslims who were less notice one of that aspect, the historical aspect. As a result, they are romanticism and apathy in the face of changing times is always changing. Unfortunately, the current methods of Islamic studies, according to the writer, are still dominated by this group. The social sciences and humanities have not received serious attention in the study of Islam. Therefore, the writer argues that this study of the need naqdiyah (criticism) in Islamic studies during this time that begins with the search for the fundamental values of Islam through the deepening of the philosophy of science and epistemology of Islam. Philosophy realized that the religious studies are something that does not separate from the authors’ point of views, inventors and originators. On the other hand, Islamic epistemology would explore various seizure hegemonies that occur in the history of Muslims. Expected epistemology is the epistemology that greet and advise each other, not the other way which claims to be the sole owner of the truth. In the reconstruction of Islamic studies, the authors offer the importance of doing multi approach to address each other as well as the presence of different methodologies. Multi approaches and methodologies that are not monolithic would make the study of Islam always answer the needs of contemporary life such as human rights, gender, environment, democracy and others. Keywords: Fundamental Values, Epistemologi Islam dan Koneksitas Pendekatan